The impact of cash flow volatility on the market leverage of listed companies in Vietnam - Hoàng, Minh Trí; Phan, Tran Duc Lien; To, Hieu Thao (Journal of Finance - Marketing Research, 2025)
This study examines the impact of cash flow volatility on the market leverage of publicly listed non-financial firms in Vietnam. Using a panel dataset of 381 firms listed on the Hanoi Stock Exchange and the Ho Chi Minh Stock Exchange from 2015 to 2024, the research employs a Feasible Generalized Least Squares (FGLS) model. The findings indicate that cash flow volatility negatively correlates with market leverage for firms in the lowest quartile of operating cash flows, while a positive correlation is observed for firms in the highest quartile. No significant relationship is found for the middle quartiles or the full sample. Additionally, industry median market leverage, firm size, and inflation positively influence market leverage, whereas the market-to-book ratio and return on total assets have negative effects. The relationship between fixed tangible assets and market leverage varies depending on firms’ cash flow levels. Using sample stratification and panel methodologies, this work refines capital structure theory and improves understanding of financing behavior under cash-flow risk. The managerial implications involve concentrating on cash-flow stabilization for low-cash enterprises, timing debt issuance for high-cash firms, and aligning leverage with industry standards to reduce financing costs. The findings support tailored debt regimes.